2010
DOI: 10.4028/www.scientific.net/amr.96.151
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Performance of Ag<sup>+</sup>-Zn<sup>2+</sup>-Zeolite Antimicrobial and Antibacterial Plastic

Abstract: Ag+-Zn2+-zeolite antimicrobial (AZZA) with high antibacterial efficiency and good color stability was prepared by ion-exchange method in water phase, followed by surface modification. Taking the modified AZZA as raw material, antibacterial polyethylene (PE) master batch was prepared and applied in PE plastic. In this paper, the technological parameters to prepare AZZA were optimized, and the effect of antimicrobial addition on the mechanical property and antibacterial property of PE plastic was studied as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Zeolites have been mentioned in several scientific reports to be utilized as favorable substrates for loading metallic ions such as silver, copper, or zinc. For instance, Xu et al 20 reported the preparation of zeolite particles charged with Ag + and Zn 2+ ions, and the addition of these particles to polyethylene through melt mixing. It has been observed that the presence of 6 wt.…”
Section: Introductionmentioning
confidence: 99%
“…Zeolites have been mentioned in several scientific reports to be utilized as favorable substrates for loading metallic ions such as silver, copper, or zinc. For instance, Xu et al 20 reported the preparation of zeolite particles charged with Ag + and Zn 2+ ions, and the addition of these particles to polyethylene through melt mixing. It has been observed that the presence of 6 wt.…”
Section: Introductionmentioning
confidence: 99%
“…The antibacterial activity of several metals (Fe, Zn, Mn, Co, Cu, Ni, V, and Mo) and their ions has been well investigated (Xu et al 2010). Inefficiency, toxicity, or cost concerns mean that only some of these elements can viably be used in industrial applications.…”
Section: Introductionmentioning
confidence: 99%